2020
DOI: 10.1007/s12630-020-01608-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient-oriented research: a new model for anesthesia in the 2lst century?

Abstract: No matter how complicated the research, or how brilliant the researcher, patients and the public always offer unique, invaluable insights. Their advice when designing, implementing and evaluating research invariably makes studies more effective, more credible and often more cost efficient as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Both confirmed that priorities of patients and caregiver prioritize improving the patient experience in perioperative care, whereas the clinicians prioritize clinical effectiveness. 83 It is unclear whether the survey respondents were a true representation of the broader surgical population 97 or could be transferable to other countries. 97…”
Section: Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Both confirmed that priorities of patients and caregiver prioritize improving the patient experience in perioperative care, whereas the clinicians prioritize clinical effectiveness. 83 It is unclear whether the survey respondents were a true representation of the broader surgical population 97 or could be transferable to other countries. 97…”
Section: Frameworkmentioning
confidence: 99%
“…83 It is unclear whether the survey respondents were a true representation of the broader surgical population 97 or could be transferable to other countries. 97…”
Section: Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…PSPs for perioperative medicine have been conducted in the UK 26 and Canada, 27 but thematic analysis identified only a 50% agreement on the resultant priorities. 27 , 28 The misalignment and disparity across the two continents confirm the need for a specific Australian perioperative medicine priority setting agenda.…”
mentioning
confidence: 98%